Egr-1 Upregulates Siva-1 Expression and Induces Cardiac Fibroblast Apoptosis - Karin Zins (International Journal of Molecular Sciences, 2014)
The early growth response transcription factor Egr-1 controls cell specific responses to proliferation, differentiation and apoptosis. Expression of Egr-1 and downstream transcription is closely controlled and cell specific upregulation induced by processes such as hypoxia and ischemia has been previously linked to multiple aspects of cardiovascular injury. In this study, we showed constitutive expression of Egr-1 in cultured human ventricular cardiac fibroblasts, used adenoviral mediated gene transfer to study the effects of continuous Egr-1 overexpression and studied downstream transcription by Western blotting, immunohistochemistry and siRNA transfection. Apoptosis was assessed by fluorescence microscopy and flow cytometry in the presence of caspase inhibitors. Overexpression of Egr-1 directly induced apoptosis associated with caspase activation in human cardiac fibroblast cultures in vitro assessed by fluorescence microscopy and flow cytometry. Apoptotic induction was associated with a caspase activation associated loss of mitochondrial membrane potential and transient downstream transcriptional up-regulation of the pro-apoptotic gene product Siva-1. Suppression of Siva-1 induction by siRNA partially reversed Egr-1 mediated loss of cell viability. These findings suggest a previously unknown role for Egr-1 and transcriptional regulation of Siva-1 in the control of cardiac accessory cell death.